Dietary mineral supplies in Malawi: spatial and socioeconomic assessment - Joy, Edward J.M.; Kumssa, Diriba B.; Broadley, Martin R.; Watts, Michael J.; Young, Scott D.; Chilimba, Allan D. C.; Ander, E. Louise (BMC, 2015)
Background Dietary mineral deficiencies are widespread globally causing a large disease burden. However, estimates of deficiency prevalence are often only available at national scales or for small population sub-groups with limited relevance for policy makers.